2023
DOI: 10.1007/s10533-023-01093-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transformation of organic matter flux through a raised bog and a blanket bog

Stephan Glatzel,
Fred Worrall,
Ian M. Boothroyd
et al.

Abstract: This study has proposed that organic matter transfer and transformation into and through a peatland is dominated by preferential loss of carbohydrates and the retention of lignin-like molecules. Here we used elemental analysis and thermogravimetric analysis to analyse the biomass, litter, peat soil profile, particulate organic matter, and dissolved organic matter fluxes sampled from a continental raised bog in comparison a maritime blanket bog. The macromolecular composition and thermodynamic analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Rebound is also occurring in a landscape that is comparatively more rugged than the HBL, with upslope catchment areas supplying mires with water and solutes. Apart from the role of topography, cold, mid and northern boreal climates are generally unfavorable for ombrogenic mires due to the influence of surface and ground water (Almquist-Jacobson & Foster, 1995;Damman, 1986;Foster & Glaser, 1986;Sallinen et al, 2023), which may promote peat decay (e.g., Glatzel et al, 2023). This soligenous water supply may be higher in northern climates due to high precipitation and low evapotranspiration during the autumn and winter period (Sallinen et al, 2023;Sjörs, 1990) compared to drier climates.…”
Section: Landscape Slope and Wetness As Drivers Of Mire Size And Shap...mentioning
confidence: 99%
“…Rebound is also occurring in a landscape that is comparatively more rugged than the HBL, with upslope catchment areas supplying mires with water and solutes. Apart from the role of topography, cold, mid and northern boreal climates are generally unfavorable for ombrogenic mires due to the influence of surface and ground water (Almquist-Jacobson & Foster, 1995;Damman, 1986;Foster & Glaser, 1986;Sallinen et al, 2023), which may promote peat decay (e.g., Glatzel et al, 2023). This soligenous water supply may be higher in northern climates due to high precipitation and low evapotranspiration during the autumn and winter period (Sallinen et al, 2023;Sjörs, 1990) compared to drier climates.…”
Section: Landscape Slope and Wetness As Drivers Of Mire Size And Shap...mentioning
confidence: 99%
“…The current mean water table depth is about 14 cm below soil surface at the central peat bog area. Peat decomposition and related CO2 and CH4 fluxes were subject of a series of research studies (Drollinger et al, 2019;Knierzinger et al, 2020;Müller et al, 2022;Glatzel et al, 2023).…”
Section: Pürgschachen Moor (Peat Bog)mentioning
confidence: 99%
“…Two papers in this collection assess the dynamics of organic matter mineralization in different peatland types. The work by Glatzel et al (2023) assesses mineralization dynamics and dissolved organic matter fluxes in two common peatland types, blanket bogs and raised bogs. They found that blanket bogs have higher hydrological C losses compared to raised bogs due to greater hydrological conductivity to the adjacent landscape.…”
mentioning
confidence: 99%